Next-generation re-sequencing of genes involved in increased platelet reactivity in diabetic patients on acetylsalicylic acid. (18th May 2016) - Postula, Marek; Janicki, Piotr K.; Eyileten, Ceren; Rosiak, Marek; Kaplon-Cieslicka, Agnieszka; Sugino, Shigekazu; Wilimski, Radosław; Kosior, Dariusz A.; Opolski, Grzegorz; Filipiak, Krzysztof J.; Mirowska-Guzel, Dagmara
Abstract: The objective of this study was to investigate whether rare missense genetic variants in several genes related to platelet functions and acetylsalicylic acid (ASA) response are associated with the platelet reactivity in patients with diabetes type 2 (T2D) on ASA therapy. Fifty eight exons and corresponding introns of eight selected genes, including PTGS1, PTGS2, TXBAS1, PTGIS, ADRA2A, ADRA2B, TXBA2R, and P2RY1 were re-sequenced in 230 DNA samples from T2D patients by using a pooled PCR amplification and next-generation sequencing by Illumina HiSeq2000. The observed non-synonymous variants were confirmed by individual genotyping of 384 DNA samples comprising of the individuals from the original discovery pools and additional verification cohort of 154 ASA-treated T2DM patients. The association between investigated phenotypes (ASA induced changes in platelets reactivity by PFA-100, VerifyNow and serum thromboxane B2 level [sTxB2]), and accumulation of rare missense variants (genetic burden) in investigated genes was tested using statistical collapsing tests. We identified a total of 35 exonic variants, including 3 common missense variants, 15 rare missense variants, and 17 synonymous variants in 8 investigated genes. The rare missense variants exhibited statistically significant difference in the accumulation pattern between a group of patients with increased and normal platelet reactivity based on PFA-100 assay. Our study suggests that genetic burden of the rare functional variants in eight genes may contribute to differences in the platelet reactivity measured with the PFA-100 assay in the T2DM patients treated with ASA.